2016
DOI: 10.1111/eos.12313
|View full text |Cite
|
Sign up to set email alerts
|

Risk of electromagnetic interference induced by dental equipment on cardiac implantable electrical devices

Abstract: Patients with cardiac implantable electrical devices should take special precautions when exposed to electromagnetic fields. Proximity to equipment used in clinical dentistry may cause interference. This study evaluated in vitro the risks associated with different types/makes of cardiac devices and types of dental equipment. Six electronic dental tools were tested on three implantable cardioverter defibrillators and three pacemakers made by different manufacturers. Overall, the risk of interference with the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…Among these 18 selected studies, 12 were in vitro and six were in vivo studies. Table 1 summarizes the details and results of the in vitro studies, 7,10–20 while the main characteristics of the in vivo studies are shown in Table 2 21–26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these 18 selected studies, 12 were in vitro and six were in vivo studies. Table 1 summarizes the details and results of the in vitro studies, 7,10–20 while the main characteristics of the in vivo studies are shown in Table 2 21–26 …”
Section: Resultsmentioning
confidence: 99%
“…This literature summarized 12 in vitro studies conducted from 2000 to 2020 and found that most dental equipment did not interfere with CIED function at the clinical application distance (20 cm). Several in vitro studies have reported that EMI affects CIED function by using EALs, 7,13 ultrasonic instruments, 10,11 battery‐operated composite curing lights, 11 diathermy, 16 electrosurgery units, 18,20 and gutta‐percha heat carriers 15 . However, in these in vitro studies, severe EMI with CIED functional changes was usually at an extremely close distance to the electrode tip or CIED generator or at the maximum sensitivity level.…”
Section: Discussionmentioning
confidence: 99%
“…Miranda ‐ Rius et al . also came to the conclusion that this was the dental tool most likely to interfere with CIEDs. In the light of these findings, we decided to include the electric pulp tester in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…In 2016, Miranda ‐ Rius et al . evaluated the in‐vitro risk of interference of six electronic dental tools and reported that the electronic apex locator has the lowest risk of producing EMIs with CIEDs.…”
Section: Discussionmentioning
confidence: 99%
“…With the booming of electronic devices and equipment over past decades, severe electromagnetic interference (EMI) and radiation pollution are brought out [1][2][3], which can easily interfere with electronic devices and also be harmful to human health [4,5]. Generally, metals with high electrical conductivity, such as copper, nickel, silver and aluminum, show good shielding performance because of the reflection of energy caused by impedance mismatch of the material and the free space [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%